THE EFFECT OF STEAMED TOFU ON SLEEP QUALITY IN PREMENOPAUSAL WOMEN - Munarifah Sulis Widyatiningsih; Sri Winarsih; Christin Hiyana Tungga Dewi (Poltekkes Kemenkes Semarang, 2021)
Background: Premenopausal syndrome in the form of hot flushes, night sweats, it can cause sleep disturbances that will affect the quality of the mother's sleep so that the mother wakes up from her sleep. Thus, natural intervention is needed in the form of isoflavone treatment by consuming processed soybeans, namely steamed tofu. The purpose of this study is knowing the effect of giving steamed tofu preparations on sleep quality in premenopausal women in Ngabean Village, Secang District, Magelang RegencyMethods: This type of research is a pre-experimental designs research with One Group Pretest Posttest research design. The measuring instrument used is the PSQI (Pittsburgh Sleep Quality Index) questionnaire. The sampling technique in this research is purposive sampling.Results: There is a significant effect of the provision of processed steamed tofu on the sleep quality of premenopausal women aged 45-50 years. This is evidenced by the results of the Wilcoxon test with p value 0.05..Conclusion: The sleep quality of premenopausal women aged 45-50 years before consuming processed steamed tofu was found in the majority in the category of poor sleep quality, which was 93.48% and after consuming processed steamed tofu was found in the majority in the category of good sleep quality, 84.78%. There is a significant effect of the provision of processed steamed tofu on the sleep quality of premenopausal women aged 45-50 years. Suggestion for premenopausal women to consuming variations of processed steamed tofu (2x a day, with a dose of @ 100 grams or medium pieces) as a source of isoflavones in improving the quality of sleep for premenopausal and postmenopausal women who experience sleep deprivation/sleep disorders in the premenopausal period so that they can undergo pre-age with totality by consuming it regularly